Pengambilan Keputusan Karir Pada Sekolah Madrasah Aliyah Al-Inayah Bandung Berdasarkan Perbedaan Jenis Kelamin - Pahri Siregar (Universitas Hamzanwadi, 2017)
The purpose of this study was to determine the career decision-making of adolescents at Al-Inayah High School in Bandung based on gender differences. Research uses a quantitative approach with a survey method. The data measurement tool is a scale questionnaire developed by Vincent A. Haren, Ph.D based on indicators of Career Decision. The research participants were students of class X, XI and XII of the Aliyah Al-Inayah Bandung Madrasah School for Academic Year 2017/2018, which consisted of 104 participants consisting of 76 women and 28 men. Based on the results obtained, the average score of career decision making for male sex is higher than female sex. The average score of men is 2.96 while women score 2.92. There are significant differences in career decision making for male gender and female gender.